how do i solve
to make it simple let y=e^x
thus giving y^3 + y - 1 = 0
y(y^2 + 1) = 1
i looked at this quickly and i don't think that you would get a solution for x.
Let y= ex and the equation becomes y3+ y- 1= 0. Can you solve that?
how can the answer be x=0?
the answer cannot be zero, i edited my post (sorry about that)
no prob, but is there really no solution?
well it makes sense to me because this is a cubic function right? how did you go about solving for y?
i didn't, i don't know how to
There is 1 real answer and 2 initial complex answers, being non-simple roots of the cubic equation they all look quite nasty.
could someone explain how to find the real answer?
Check out Mathworld's page on the cubic equation.
you can set
then the equation will become [tex] y+y^3-1=0 [/tex]
now you can creat the term [tex] y^2 [/tex],then minus the same term.
Separate names with a comma.